Bose–Einstein condensation of two-dimensional spin-1 Cooper pairs in a uniform magnetic field. (1st October 2022) - Cheng, Ze
Abstract: Bose–Einstein condensation of two-dimensional spin-1 Cooper pairs in a uniform magnetic field is investigated within the framework of quantum statistical mechanics. We derive an exact analytical solution of two-dimensional spin-1 Cooper pairs in a uniform magnetic field, which involves a q -digamma function in mathematics. In two dimensions, it is found that the critical temperature and condensate fraction are monotonically increasing functions of magnetic field B, Landé factor g, and number density σ . Our investigation in two dimensions provides an example of the magnetic-field-tuned insulator-superconductor quantum phase transition.